Herd Behavior in Organizations: The Case of Entering an Investment Project - Adam Karbowski (Zeszyty Naukowe KGŚ, 2011)
In the following paper the author applies concepts of information economics (hidden characteristics and signaling) to decision-making processes in the hierarchical organizations. The case of entering an investment project by the company is thoroughly examined. The aim of the paper is to identify and explain managerial decision biases and risk of herd behavior formation in hierarchical organizational structures. The explanation is structured in a simple mathematical model and equipped with concise economic discussion.
Keywords: D21; D23; 330; herd behavior; decision-making; organizations; information economics; Behavioral economics